Suicide Risk and Resiliency Factors Among Hispanic Teens in New Mexico: Schools Can Make a Difference. (4th February 2018) - Hall, Meryn; Fullerton, Lynne; FitzGerald, Courtney; Green, Dan
ABSTRACT: BACKGROUND: Youth suicide is a serious public health problem in the United States. School environments, and the attention of school adults, are promising but minimally studied avenues for promoting mental health among students. METHODS: The 2013 New Mexico Youth Risk and Resiliency Survey data were analyzed to identify ways in which the school environment influences suicide attempts in a sample of Hispanic students. Factors examined were: relationships with school adults, speaking a language other than English at home, being born outside the United States and not having enough to eat. Odds ratios were used to measure relationships. RESULTS: Factors influencing suicide attempt were similar for boys and girls. The odds of suicide attempt declined by approximately one third as measures of positive relationships with school adults increased. Post‐high school education plans also were protective. Being born outside the United States and not having enough to eat increased the odds of past‐year suicide attempt. Speaking a language other than English at home was a weak risk factor for suicide attempt only among Hispanic girls. CONCLUSIONS: Teachers and other school adults can decrease suicide risk for Hispanic teens by forming supportive relationships with students. Special consideration should be given to providing free breakfast in schools.